Escola e preconceito : relações raciais na ótica dos professores - Santos, Carina Feitosa dos (2014)
The present study aims to examine racism in schools from the placement of teachers in front of their demonstration and assignments of responsibility for its occurrence. Structured into five chapters, the first, are addressed the definitions of prejudice, discrimination and racism, the influence of social norms that can lead to what has been termed |new prejudices| and |new racism| plus some aspects about how racism has been characterized in Brazil since the abolition until the present day. In the second chapter, considerations about the reflection of the previously discussed constructs in the school environment are shown. We highlight the role assigned to the school and the teacher in the propagation and fight against prejudice and racism other than affirmative action geared to this purpose, as the 10.639/03 law. Data collection was done through the application of a questionnaire with open and closed questions, which was applied to 69 teachers of public schools in the cities of Aracaju and Lagarto, Sergipe. The data were subjected to analysis of frequency and multivariate analyses with the help of SPSS and IRAMUTEQ software. The results point to a rejection of the issue by the teachers and a tendency to recognize the influence of racial bias when in reference to the context of the schools in general, but a denial of its existence or influence in the school environment where they operate. About possible measures with the purpose of modifying the framework of racism in schools, teacher´s discourse suggests, as a measure to be adopted, a less emphasis given to skin color, positioning that seems to oppose the principle governing the affirmative actions designed for this purpose. It is suggested the use of discourse and of the reactions submitted by teachers about racism in schools in the development of effective actions to combat racism in schools.